Tingkat Cemaran Escherichia Coli pada Susu Segar dari Peternakan Sapi Perah di Surabaya - Sheila Marty Yanestria (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2015)
The quality of milk is important to supply healthy milk for consumers. The increase of bacteria in fresh milk is one factor that can decrease the quality of milk. Bacteria in fresh milk can harm the health of consumers if the milk is not processed properly. Escherichia coli is a bacteria that often contaminate fresh milk. Escherichia coli can be pathogenic in humans because of some serotypes of this bacteria is able to produce the toxin. This toxin can cause fluid accumulation in the intestine and diarrhea. The purpose of this study was to determine the contaminant levels of Escherichia coli in fresh milk from dairy farms in Surabaya. The method used to determine the contaminant levels of Escherichia coli is Most Probable Number (MPN). The results showed that the average of Escherichia coli contaminant levels in fresh milk from dairy farms in Surabaya is 110 Escherichia coli / ml. This is not appropiate with the requirements of ISO 7388: 2009 (<3 Escherichia coli / ml).